2022
DOI: 10.3390/min12121579
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Chemical Elements and Their Geochemical Baseline Values in Surface Water of the Parauapebas River Basin, Southeast Amazon, Brazil

Abstract: The present work aims to evaluate the chemical quality and establish the geochemical baseline values of elements in the surface waters of the Parauapebas River basin (PRB), which is one of the major subbasins in the Itacaiúnas River watershed (IRW) located in the Brazilian Amazon. A total of 327 surface water samples were collected during the rainy and dry seasons in 2017. Results indicate that waters are slightly acidic to alkaline (pH 6 to 8), and there was a strong influence of the seasonal variation on wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Another hydrogeochemical research concerns the occurrence and source of toxic minerals in rivers, including but not limited to (heavy) metals such as mercury, arsenic, manganese, copper and iron [132, [153][154][155][156][157]. Though human activity is often seen as a source of pollution, research has shown that human activity is only partly to blame for the presence of polluting minerals [132,155], or that all pollution seems to be geogenic (i.e.…”
Section: (I) Geological Influence On Hydrological Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Another hydrogeochemical research concerns the occurrence and source of toxic minerals in rivers, including but not limited to (heavy) metals such as mercury, arsenic, manganese, copper and iron [132, [153][154][155][156][157]. Though human activity is often seen as a source of pollution, research has shown that human activity is only partly to blame for the presence of polluting minerals [132,155], or that all pollution seems to be geogenic (i.e.…”
Section: (I) Geological Influence On Hydrological Diversitymentioning
confidence: 99%
“…Though human activity is often seen as a source of pollution, research has shown that human activity is only partly to blame for the presence of polluting minerals [ 132 , 155 ], or that all pollution seems to be geogenic (i.e. originating from the natural environment) [ 153 , 154 , 156 , 157 ]. Moreover, the chemical characteristics of water are strongly influenced by seasonal variations [ 154 ].…”
Section: Geodiversity Components In the Amazon Drainage Basinmentioning
confidence: 99%
See 1 more Smart Citation